Identification of a lipase gene with a role in tomato fruit short‐chain fatty acid‐derived flavor volatiles by genome‐wide association. (3rd September 2020) - Li, Xiang; Tieman, Denise; Liu, Zimeng; Chen, Kunsong; Klee, Harry J.
SUMMARY: Fatty acid‐derived volatile organic compounds (FA‐VOCs) make significant contributions to tomato ( Solanum lycopersicum ) fruit flavor and human preferences. Short‐chain FA‐VOCs (C5 and C6) are among the most abundant and important volatile compounds in tomato fruits. The precursors of these volatiles, linoleic acid (18:2) and linolenic acid (18:3), are derived from cleavage of glycerolipids. However, the initial step in synthesis of these FA‐VOCs has not been established. A metabolite‐based genome‐wide association study combined with genetic mapping and functional analysis identified a gene encoding a novel class III lipase family member, Sl‐LIP8, that is associated with accumulation of short‐chain FA‐VOCs in tomato fruit. In vitro assays indicated that Sl‐LIP8 can cleave 18:2 and 18:3 acyl groups from glycerolipids. A CRISPR/Cas9 gene edited Sl‐LIP8 mutant had much lower content of multiple fruit short‐chain FA‐VOCs, validating an important role for this enzyme in the pathway. Sl‐LIP8 RNA abundance was correlated with FA‐VOC content, consistent with transcriptional regulation of the first step in the pathway. Taken together, our work indicates that glycerolipid turnover by Sl‐LIP8 is an important early step in the synthesis of multiple short‐chain FA‐VOCs. Significance Statement: Reduced flavor in modern commercial tomatoes is a major consumer concern. Flavor is a highly complex trait involving many volatile chemicals synthesized via multiple biosynthetic pathways that all contribute to consumer liking. Elaborating their biosynthetic pathways and their regulation is a major step toward flavor improvement. Short chain fatty acid‐derived volatiles make significant contributions to fruit flavor. A metabolite‐based genome‐wide association study combined with genetic mapping and functional analysis identified a gene encoding a class III lipase family member, Sl‐LIP8, that is associated with accumulation of these volatiles in fruit. In vitro and in vivo functional analysis indicates that glycerolipid turnover by Sl‐LIP8 is an important early step in the synthesis of multiple short‐chain FA‐VOCs.